Minerals and Heavy Metal Composition in Seaweeds of the Eastern Coast, Northern Bay of Bengal, Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
This study aimed to analyze minerals (Ca, Mg, Fe, Zn, Mn and Cu) and heavy metals (Pb and Cd) content of seaweeds collected from coastal waters of Bangladesh using Atomic Absorption Spectrophotometer (AAS). Eight wild species in three phyla viz. Rhodophyta (Hypnea sp.), Chlorophyta (Enteromorphasp.),and Phaeophyta (Sargassumsp.,Hydroclathrusclathratus, Padinapavonica, Colpomeniasinuosa, Petalonia fascia and Dictyotaciliolata)and one cultured Rhodophyta species viz. Hypnea sp. were collected from St. Martin’s Island and Cox’s Bazar, respectively. Results showed minerals and heavy metals concentrations were varied from species to species. Ca concentration was the highest in Phaeophyta (18565 mg/kg-dw) and it was 19 times higher than the value reported in Chlorophyta (950 mg/kg-dw). In contrast, Fe, Zn and Mn were the highest in Rhodophyta. This is because different groups of seaweeds affinity to absorb minerals depend on environmental parameters for example salinity, pH and light intensity, mineral accessibility in sea water and interactions between elements, growth and metabolic factors, etc. Ca content was the highest in C. sinuosa (30890 mg/kg-dw), whereas, it was the lowest in cultured Hypnea sp. (120 mg/kg-dw). P.pavonica showed the highest concentrations of Fe (15030 mg/kg-dw), Zn (33.46 mg/kg-dw) and Mn (443.79 mg/kg-dw). Mineral contents of cultured seaweeds were comparatively lower than the wild species. Results showed mineral concentrations in all seaweeds were relatively greater than heavy metals. However, wild Hypneasp. contained slightly 2 times higher Cd (2.11 mg/kg-dw) than the cultured Hypnea sp. (0.98 mg/kg-dw) due to higher level of anthropogenic source of pollution in St. Martin’s Island. Heavy metal contamination in seaweeds might raise health concerns among the consumers. Findings of this study might help to unleash minerals and heavy metals compositions of the studied seaweeds of Bangladesh. Policy makers can formulate and establish health safety guidelines for safe consumption of seaweeds.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(2), 2021, P 43-52